2011
DOI: 10.1590/s1516-89132011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of whey from bovine colostrum and mature milk

Abstract: The aim of this study was to standardize a methodology to obtain two-dimensional (2D) maps of whey proteins from bovine colostrum and mature milk, using two-dimensional electrophoresis, in order to identify the minor proteins by matrix-assisted laser desorption/ionization tandem time-of-flight mass spectrometry (MALDI TOF/TOF MS).A total of 38 proteins were identified, 20 spots in the colostrum whey and 18 in the mature milk whey; 5 of them were identified for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Presently, several depletion kits for high abundance proteins removal are available, although their use has generated some controversy (Hernández-Castellano et al 2014b). In agreement with this statement, Golinelli et al (2011) observed that the treatment with the Albumin and IgG removal kit was ineffective in removing IgG and BSA from the bovine colostrum whey. It is known that the albumin and IgG removal kit contains agaroseimmobilised anti-IgG against human proteins.…”
Section: Colostrum and Milk Proteomicsmentioning
confidence: 88%
“…Presently, several depletion kits for high abundance proteins removal are available, although their use has generated some controversy (Hernández-Castellano et al 2014b). In agreement with this statement, Golinelli et al (2011) observed that the treatment with the Albumin and IgG removal kit was ineffective in removing IgG and BSA from the bovine colostrum whey. It is known that the albumin and IgG removal kit contains agaroseimmobilised anti-IgG against human proteins.…”
Section: Colostrum and Milk Proteomicsmentioning
confidence: 88%
“…The main objective of this computational data aggregation from 20 publications, with 35 datasets (Table 2), is to obtain an overview of milk proteins independently of breed, age, country and methodologies of protein isolation and identification. Methods for protein isolation were density gradient ultracentrifugation 15,39 , centrifugation and washing 10,22,40 , (ultra)centrifugation with acidification 48 and with major proteins depletion 42,45,46 , or (ultra)centrifugation without acidification 13,17,41,43,44,47,4953 .…”
Section: Methodsmentioning
confidence: 99%
“…Methods for protein identification were FASP, dimethyl labelling, LC-LTQ-Orbitrap/MS 44 , electrophoresis gel LC-MS/MS 52 , iTRAQ labelling, SCX and LC-MS/MS 10,22,39,43,48 , Maldi-(TOF/TOF)-MS detection 42,47,49,50 and from 1 to 15 repetitions of (nano)LC-MS/MS runs 13,15,17,40,41,45,46,51,53 . Protein identifiers ( ID ) reported in the publications were extracted from tables in Portable Document Format (PDF) or from supplementary data files using Tabula software (www.tabula.technology, Last update February 11, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The different results may be accounted for by changes in the composition of the milk, which can occur due to the season, animal nutritional status and health, and stage of lactation (Heck et al, 2009;Golinelli et al, 2011). Biogenic Amines.…”
Section: Discussionmentioning
confidence: 99%